A new raninoid crab (Decapoda, Brachyura, Raninidae) from the early Oligocene (late Rupelian) of Italy - Giovanni Pasini; Alessandro Garassino (Natural History Sciences, 2017)
Pasini & Garassino (2017) did a preliminary systematic review of the worldwide fossil species of Ranina, pointing out that it was used as “basket genus” for almost two centuries to accommodate different questionable taxa pertaining or not to Raninoidea. The result was that just four species were possibly assigned to Ranina compared to 23 species previously listed by Karasawa et al. (2014). Among the studied species, a rich sample of specimens from the early Oligocene of the Ligure-Piemontese Basin (Italy), previously assigned to Ranina speciosa by Ristori (1889) and Allasinaz (1987), has been revised and here discussed. The studied specimens are herein assigned to the new genus Alcespina, with A. ovadaensis n. sp (Raninidae), whereas five specimens of Allasinaz’s original sample are assigned to Raninoides H. Milne Edwards, 1837. Finally, this study allows us to review the questionable species Ranina berglundi Squires & Demetrion, 1992, from the early Eocene of Mexico, herein also assigned to A. berglundi (Squires & Demetrion, 1992) n. comb.